2011
DOI: 10.1002/fld.2210
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in drag and vortex shedding frequency through porous sheath around a circular cylinder

Abstract: SUMMARYA numerical study on the laminar vortex shedding and wake flow due to a porous-wrapped solid circular cylinder has been made in this paper. The cylinder is horizontally placed, and is subjected to a uniform cross flow. The aim is to control the vortex shedding and drag force through a thin porous wrapper around a solid cylinder. The flow field is investigated for a wide range of Reynolds number in the laminar regime. The flow in the porous zone is governed by the Darcy-Brinkman-Forchheimer extended mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 33 publications
(46 reference statements)
2
30
0
Order By: Relevance
“…Based on Ergun's model [39], the porous medium can be represented using particles of mean diameter d p . The method used to model the flow transport within the porous material in this paper is similar to that of Bhattacharyya and Singh [40] and Bae et al [41,42].…”
Section: Methodsmentioning
confidence: 94%
“…Based on Ergun's model [39], the porous medium can be represented using particles of mean diameter d p . The method used to model the flow transport within the porous material in this paper is similar to that of Bhattacharyya and Singh [40] and Bae et al [41,42].…”
Section: Methodsmentioning
confidence: 94%
“…It is further found that, as the asymmetric cross section of the cylinder causes the wake centerline to shift toward the sharp corner side of the bluff body, the wake remains globally symmetric about the shifted centerline. A numerical study on the laminar vortex shedding and wake flow due to a porous-wrapped solid circular cylinder has been made by Bhattacharyya and Singh [13]. The laminar vortex shedding behind a porous-wrapped solid cylinder was investigated for Reynolds number up to 250.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of permeability on the flow transition from steady to periodic viscous flow was studied for the case of an unbounded solid circular cylinder wrapped in a porous layer by Bhattacharyya and Singh (Bhattacharyya and Singh, 2011) and also for the case of an unbounded porous square cylinder by Babu and Narasimhan (Babu and Narasimhan, 2010) and by Jue (Jue, 2004). These studies show that high permeability ( > 10 −4 ) dampens the vortex shedding behind the cylinder.…”
Section: 4)mentioning
confidence: 99%